Leucine-Rich Glioma Inactivated-1 and Voltage-Gated Potassium Channel Autoimmune Encephalitis Associated with Ischemic Stroke: A Case Report - McGinley, Marisa; Morales-Vidal, Sarkis; Ruland, Sean (Frontiers in Neurology, 2016)
Autoimmune encephalitis is associated with a wide variety of antibodies and clinical presentations. Voltage gated potassium channel (VGKC) antibodies are a cause of autoimmune non-paraneoplastic encephalitis characterized by memory impairment, psychiatric symptoms, and seizures. We present a case of VGKC encephalitis likely preceding an ischemic stroke. Reports of autoimmune encephalitis associated with ischemic stroke are rare. Several hypothesizes linking these two disease processes are proposed.